Operational Issues Related to the Functioning of Interbank Foreign Exchange Markets in Selected African Countries - Lum, Yin-Fun (IMF Working Papers; Working Paper ;, 1994)
This paper discusses the main operational issues involved in the implementation of interbank foreign exchange systems in selected African countries. The countries considered are The Gambia, Ghana, Kenya, Mozambique, Nigeria, and Sierra Leone. The paper finds that exchange rates in these markets tend to be determined through transactions between dealers and clients at the retail level, for the most part, rather than through wholesale interdealer transactions. Additionally, many factors continue to limit the full development of these markets. In particular, informational problems limiting 'real time' quotes, inadequate competition in the market, and insufficient regulations to reduce exchange rate risk and encourage 'true' interdealer transactions. Despite these limitations, the markets studied have improved the efficiency of foreign exchange allocation and substantially narrowed exchange rate differentials between the official and parallel markets.